Demonstration of UV-A stimulated emission from optical pumping with a nano-porous cladding layer - Yifan Yao; Toru Inatome; Ibraheem Aljarboua; Hanyu Bi; Julia Didziulis; Michael Iza; Mattanjah de Vries; Shuji Nakamura; Abdullah Almogbel; Steven P. DenBaars (Applied Physics Express)
We report a room-temperature ultraviolet-A (UV-A) stimulated emission from a multiple-quantum-well laser diode featuring a nano-porous bottom cladding layer on the GaN substrate. For a 1500×15 μ m ridge-type edge-emitting laser, we achieved a 372.8 nm emission under optical pumping, with a full-width-half-maximum (FWHM) of less than 2 nm and a threshold optical pumping power density of less than 1.2 MW cm ^−2 . The integration of a nano-porous cladding layer effectively minimizes lattice mismatch, enhances confinement factor, and maintains electrical conductivity. This demonstration expands the potential for developing high-performance UV laser diodes on GaN substrates, overcoming limitations previously imposed by critical thickness contrasts.